2018
DOI: 10.1002/chem.201800320
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Chemical Reactivity of Phosphonium‐Based Ionic Liquids with Tellurium

Abstract: The chemical reactivity of phosphonium based ionic liquids (ILs) towards tellurium at temperatures above 220 °C was systematically investigated by a series of dissolution experiments, tracking the solute tellurium species by nuclear magnetic resonance, and characterizing the reaction products by X‐ray diffraction and scanning electron microscopy. The initial step is the thermal elimination of an alkyl group of the phosphonium cation of the ILs, most probably via an SN2 mechanism. The addition of tellurium foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 44 publications
1
22
0
8
Order By: Relevance
“…At 200 °C, the used ILs decompose under formation of trialkylphoshane species ( R 3 P) [27] . The Lewis bases R 3 P are known to react with tellurium [26,28] . Reducing the reaction temperature to 105 °C led to single phase telluride in [P 66614 ]Cl and [BMIm]Cl as well as to an extension of the reaction time necessary for full conversion from 4 h to 16 h. In [P 66614 ]Cl, full conversion to Ag 2 Te is achieved even at 60 °C (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…At 200 °C, the used ILs decompose under formation of trialkylphoshane species ( R 3 P) [27] . The Lewis bases R 3 P are known to react with tellurium [26,28] . Reducing the reaction temperature to 105 °C led to single phase telluride in [P 66614 ]Cl and [BMIm]Cl as well as to an extension of the reaction time necessary for full conversion from 4 h to 16 h. In [P 66614 ]Cl, full conversion to Ag 2 Te is achieved even at 60 °C (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…[35] Ruck and co-workers showed that quaternary phosphonium cations of ILs can undergo decomposition in the presence of Se/Teabove 220 8 8C. [110,111] Aseries of dissolution tests,i nw hich the solute Se/Tes pecies were tracked by nuclear magnetic resonance (NMR) spectroscopy, was applied to systematically investigate the decomposition mechanisms.These studies indicate that one alkyl substituent of the quaternary phosphonium cations is eliminated through an S N 2decomposition pathway,leading to dissolution of Se/Te through the formation of the corresponding trialkylphosphane selenides/tellurides (Figure 4). However,t he decomposition mechanism of the phosphonium IL in the presence of Te is much more complicated than that in the presence of Se.…”
Section: Reactions Of Chalcogen-containing Ionic Liquidsmentioning
confidence: 99%
“…e) Bi 2 Te 3 nanoplate.f)Flower-like Bi 2 Te 3 particle. Reproducedwith permission [111]. Copyright 2018, Wiley-VCH.g -i)3Dcomplex Te microstructures.…”
mentioning
confidence: 99%
“…[35] Ruck et al zeigten, dass sich quartäre Phosphonium-Kationen von ILs in Anwesenheit von Se/Tebei Te mperaturen über 220 8 8C zersetzen. [110,111] In einer Reihe von Lçsungsversuchen, in welchen die gelçsten Se/Te-Spezies mit Kernspinresonanzspektroskopie (NMR) verfolgt wurden, konnte der Zersetzungsmechanismus systematisch untersucht werden. Diese Experimente zeigen, dass ein Alkylsubstituent über eine S N 2-Reaktion eliminiert wird.…”
Section: Reaktionen Chalkogenhaltiger Ionischer Flüssigkeiten (Einschließlich Reaktionen Ionischer Flüssigkeiten Mit Chalkogenen)unclassified
“…Mit geringeren Mengen Te verschwinden die 125 Te -Satellitenpeaks,und die Dubletts im 125 5c,d,g-i). [111,112] [BMIm][SCN] als Lçsungsmittel und Schwefelquelle in der Synthese von CdS-Nanokompositen dienen kann. [113] Zheng et al entwarfen die Se-haltige IL [BMIm][SeO 2 (OCH 3 )] als neuartige Se-Quelle.…”
Section: Reaktionen Chalkogenhaltiger Ionischer Flüssigkeiten (Einschließlich Reaktionen Ionischer Flüssigkeiten Mit Chalkogenen)unclassified